The abnormal “new normal”: The concept of the “new normal” as a framing structure in social media discourse: A cognitive-discursive analysis - Sahverdova, Nava Vanda (Slavica, 2025)
This study is devoted to the analysis of the concept of the "new normal" and the description of its frame structure in everyday usage within social media discourse. Based on a cognitive-discursive approach, the study examines the transformation of the meaning of the expression "the new normal" from its original economic-political term into a polysemous linguistic tool for expressing evaluation, anxiety, and rejection. Using comments from social media platforms (such as Facebook, Telegram, and LiveJournal), the study identifies frames and thematic groups in which this concept is actualized: the moral and value devaluation, the cultural-civilizational crisis, ideological pressure, the normalization of violence, the mediatization of tragedies, and the social adaptation to post-COVID realities. The analysis shows that the "new normal" functions in media discourse as a marker of normative transformation and a cognitive representation of crisis phenomena. The concept serves as an ironic label, a means of stigmatization, emotional evaluation, and as a tool for expressing identity and describing the "other" amid global and local changes.